2021
DOI: 10.2147/tcrm.s320145
|View full text |Cite
|
Sign up to set email alerts
|

High Pretreatment Platelet-to-Albumin Ratio Predicts Poor Survival Results in Locally Advanced Nasopharyngeal Cancers Treated with Chemoradiotherapy

Abstract: In a lack of similar research, we assessed the prognostic utility of pretreatment platelet-to-albumin ratio (PAR) in locally advanced nasopharyngeal carcinoma (LANPC) patients managed with concurrent chemoradiotherapy (CCRT). Patients and Methods: Present retrospective analysis included a sum of 128 consecutively treated LANPC patients who underwent cisplatinum-based radical CCRT. Availability of an ideal pretreatment PAR cutoff that may stratify the study population into two cohorts with significantly distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In addition to reflecting the nutritional status of the body, ALB is considered to be associated with inflammation ( 22 , 23 ). It is proposed that a new indicator PAR that combines the above two might be able to better reflect the body’s inflammatory state ( 24 ). Chronic inflammation undoubtedly participated in the pathogenesis and development of IgAN, and inflammatory mediators might damage the structure and function of the kidney tissue ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reflecting the nutritional status of the body, ALB is considered to be associated with inflammation ( 22 , 23 ). It is proposed that a new indicator PAR that combines the above two might be able to better reflect the body’s inflammatory state ( 24 ). Chronic inflammation undoubtedly participated in the pathogenesis and development of IgAN, and inflammatory mediators might damage the structure and function of the kidney tissue ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PAR has the ability to accurately reflect the status of immune system, systemic inflammation, and nutritional status of the patient simultaneously after considering the individual functions of PLTs and ALB. 12 Additionally, past investigations on the prognostic worth of PAR showed that the preoperative PAR was significantly associated with the patients' prognoses in pancreatic adenocarcinomas and non-small cell lung carcinomas. 9,10 A few previous studies have reported all cases that occurred between April and October, 14,17 This is consistent with our conclusions, that after grouping by year and quarter, it can be observed that the main infection time distribution was primarily found in the second and third quarters (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…6 A number of previous studies have reported that the pathogenesis of SFTS is related to abnormal immune response. 7,8 Moreover, additional recent findings have confirmed that platelet-albumin ratio (PAR) can be used as a potential marker of inflammation in patients, and can serve as a prognostic factor or progression indicator for a variety of diseases, [9][10][11][12] For instance, preoperative PAR has been found to be a useful and potential prognostic biomarker in patients with non-small cell lung cancer undergoing primary resection. 9 Preoperative PAR has also been described as a novel and effective independent prognostic indicator of survival after pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the platelet-to-albumin ratio (PAR) was developed and reported as a promising prognostic factor in gastrointestinal malignancies (11)(12)(13). Previous reports have shown that platelets are a marker of the systemic inflammation status, and albumin is one of the most important markers of nutritional status.…”
mentioning
confidence: 99%